Yusfull cloth line / Muhammad Yusfaiz Yusham … [et al.] - Yusham, Muhammad Yusfaiz; Othman, Amirul Hakim; Kamaruddin, Norfaradila; Abu Husin, Nur Na'eimah; Aziz, Azahari; Mohamad Nasir, Ahmad Kamal; Md Taib, Norraeffa (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
Cloth line for window is an invention that can be placed at the window, especially at home, such as flats, apartments and hostels. It does not require any (drilling) on the wall. This cloth line is using the method of "open-use, fold-store'' OUFS. It can be fold into smaller form so that it can be easily store at any place. The advantages are to save spaces and solve the problem of space for hanging clothes. It may attract those people who live in multistorey house. This product is most likely targeted to be commercializing to consumer who lives at apartment, flat etc. Instead of increasing the job opportunity it also affect the standard of live. Lifestyle is easier using this new technology.